KEBUTUHAN DEBIT UNTUK FLUIDISASI 01 MUARA SUNGAI- DAN ALUR PELAYARAN - Wahyu Widiyanto (Universitas Negeri Yogyakarta, 2005)
ABSTRACTFluidization method is one of the alternatives to maintain river mouth andharbour entrance. It is expected to substitute the role of maintenance dredgingthat is high cost and often inefficient for small volume of dredging. A series ofresearch is conducted to understand the fluidization method but there has beenlittle confidence whether fluidization process can run when the system isimplemented in the field. Hence, fluidization model of large scale is expected toenhance confidence.The objective of the present study is to obtain flow rate required forfluidization. The study used two dimensional physical modelling of large scale. Itwas conducted by testing various sediment thickness (burial depth of pipe) from25 cm to 150 cm in a large concrete well. Several parameters were observed onthe experiments. Performances of one and three holes of fluidizer pipe wereobserved too.The flow rate requirement increases linearly with sediment thickness. For 1hole of fluidizer pipe, the flow rate requirement approaches Qh =0,45 db + 0,40.While 3 holes of fluidizer pipe requires flow rate as Qh =1,44 db + 0,16. Wheredb is sediment thickness. Comparison between the performances of 1 holeand 3 holes of pipe show that holes spacing significant to fluidization. Thedistance between holes should not be too long. Cooperation of holes mayreduce flow rate requirement.Keywords : fluidization, dredging, sediment